HUBUNGAN DERAJAT PERLEMAKAN HATI NON-ALKOHOLIK DENGAN AKTIVITAS AMINOTRANSFERASE SERUM - Yustiani, Nyoman Trisna; ., Mutmainnah; Arif, Mansyur (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2018)
Fatty liver could be related to alcoholic or non-alcoholic. Mild to moderate elevation of serum aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities are the most laboratories test ordered in patient with non-alcoholic fatty liver. This study has purposed to know the relation of degree non-alcoholic fatty liver’s with aminotransferase serum activity. A cross-sectional study was done in 38 patients with non-alcoholic fatty liver aged 30 to 60 years at Clinical Pathology Laboratory Installation and Radiology Department Dr. Wahidin Sudirohusodo Hospital in Makassar from March to July, 2008. Patient made to criteria done some laboratory test for AST and ALT examination. Data was analyzed using T-Test in SPSS for windows version 11,5. In this study we found that there were a significant difference between non-alcoholic fatty liver degree with AST and ALT activity in cutt off 18 (p < 0,05). From this study we could conclude that the activity of AST and ALT serum can be used to predict probability of non-alcoholic fatty liver.